Effects of SKF83959 on the excitability of hippocampal CA1 pyramidal neurons: a modeling study - Zhou Shang-lin; Chu Hong-yuan; Jin Guo-zhang; Cui Jian-min; Zhen Xue-chu (Acta Pharmacologica Sinica; Vol 35, No 6 (June 2014): Acta Pharmacologica Sinica, 2016)
Shang-lin ZHOU1, 2, *, Hong-yuan CHU1, 2, Guo-zhang JIN1, Jian-min CUI3, Xue-chu ZHEN1, 3, * 1Department of Pharmacology II, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai 201203, China; 2University of Chinese Academy of Sciences, Beijing 100049, China; 3Jiangsu Key Laboratory of Translational Research and Therapy for Neuropsychiatric Disorders & Department of Pharmacology, College of Pharmaceutical Sciences, Soochow University, Suzhou 215123, China Aim: 3-Methyl-6-chloro-7,8-hydroxy-1-(3-methylphenyl)-2,3,4,5-tetrahydro-1H-3-benzazepine (SKF83959) have been shown to affect several types of voltage-dependent channels in hippocampal pyramidal neurons. The aim of this study was to determine how modulation of a individual type of the channels by SKF83959 contributes to the overall excitability of CA1 pyramidal neurons during either direct current injections or synaptic activation. Methods: Rat hippocampal slices were prepared. The kinetics of voltage-dependent Na+ channels and neuronal excitability and depolarization block in CA1 pyramidal neurons were examined using whole-cell recording. A realistic mathematical model of hippocampal CA1 pyramidal neuron was used to simulate the effects of SKF83959 on neuronal excitability. Results: SKF83959 (50 μmol/L) shifted the inactivation curve of Na+ current by 10.3 mV but had no effect on the activation curve in CA1 pyramidal neurons. The effects of SKF83959 on passive membrane properties, including a decreased input resistance and depolarized resting potential, predicted by our simulations were in agreement with the experimental data. The simulations showed that decreased excitability of the soma by SKF83959 (examined with current injection at the soma) was only observed when the membrane potential was compensated to the control levels, whereas the decreased dendritic excitability (examined with current injection at the dendrite) was found even without membrane potential compensation, which led to a decreased number of action potentials initiated at the soma. Moreover, SKF83959 significantly facilitated depolarization block in CA1 pyramidal neurons. SKF83959 decreased EPSP temporal summation and, of physiologically greater relevance, the synaptic-driven firing frequency. Conclusion: SKF83959 decreased the excitability of CA1 pyramidal neurons even though the drug caused the membrane potential depolarization. The results may reveal a partial mechanism for the drug’s anti-Parkinsonian effects and may also suggest that SKF83959 has a potential antiepileptic effect. Keywords: SKF83959; hippocampus; pyramidal neuron; neuronal modeling; excitability; Na+ channel; EPSP; temporal summation This work was financially supported by grants from the National Natural Science Foundation of China (81130023, 31373382, and 31271143) and the National Basic Research Plan (973) of the Ministry of Science and Technology of China (2011CB5C4403). We are also grateful for support from the Priority Academic Program Development of Jiangsu Higher Education Institutes (PAPD). * To whom correspondence should be addressed. E-mail zhoushanglin@gmail.com (Shang-lin ZHOU); zhenxuechu@suda.edu.cn (Xue-chu ZHEN) Received 2013-11-26 Accepted 2014-03-03